Precision technologies and their relationship with the management of agricultural inputs in the context of sustainability in vulnerable regions - Santillán-Gonzáles, Manuel (2025)
This research analyzes the relationship between the use of precision technologies and the management of agricultural inputs within the framework of sustainability. Structured surveys were conducted with 120 producers, addressing variables such as access to technology, training, technological integration, productivity, and barriers. Multiple linear regression, Spearman correlation, and cluster analysis were applied to identify the factors influencing efficient, environmentally responsible, and socioeconomically viable input management. The findings show that the Productivity and Sustainability dimension has a significant positive effect, while barriers and challenges have a negative influence. The model related to soil health (adjusted R² = 0.304) highlights the potential of precision technologies to enhance yield and reduce environmental impacts. However, structural limitations, such as high costs, insufficient infrastructure, and lack of training, were identified as major obstacles to adoption. The results emphasize the need for public policies, technical training programs, and support strategies to foster more sustainable, resilient, and inclusive agricultural systems aligned with the Sustainable Development Goals.